Pre-Implementation Priorities in School-Based Health Programmes: A CFIR-Informed Study of School Leadership Perspectives (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Pre-implementation – referring to the planning, preparation, and organisational alignment that occurs before an intervention is delivered – is a critical but often overlooked determinant of implementation success. This study investigates key factors shaping the pre-implementation of the “Generation Healthy Kids” (GHK) programme in Danish primary schools, using the Consolidated Framework for Implementation Research (CFIR). Focus is on how different levels of school leadership perceive what conditions must be in place to support future readiness and staff engagement.Methods: The study involved 43 school management representatives – principals, vice principals, deputy heads, and department heads – from 22 of the 23 schools participating in GHK. These schools were evenly distributed across the intervention (n = 11) and control groups (n = 11). Participants completed an online questionnaire addressing pre-implementation conditions within the CFIR domains ‘Inner Setting’ and ‘Implementation Process’. The pre-implementation phase was defined as the period from each school’s formal decision to participate until notification of allocation to intervention or control group. Descriptive statistics were used to compare responses between school leadership (principals, vice principals, deputy heads) and department heads.Results: A total of 37 representatives completed (n = 34) or partly completed (n = 3) the questionnaire. Of these, 19 responses came from intervention schools and 18 from control schools. While both groups identified management support as the most critical condition, their priorities diverged. School leaders emphasised logistical enablers – such as preparation time and facility access – during pre-implementation. Department heads highlighted staff competency development and early monitoring of staff engagement, indicating a need for time and support prior to implementation. These differences reflect the distinct responsibilities and perspectives of the two groups.Conclusion: The findings underscore the importance of understanding leadership-specific priorities in the pre-implementation phase. A one-size-fits-all strategy is unlikely to suffice; instead, tailored approaches that reflect the roles and responsibilities of different leadership levels are needed to strengthen planning and coordination. Future studies should expand the stakeholder perspective to include teachers, students, and municipal actors to support comprehensive pre-implementation planning and improve school readiness for implementationSupport/Funding Source: This study was funded by the Novo Nordisk Foundation.